2011
DOI: 10.1007/s10529-011-0645-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages overexpressing VEGF, transdifferentiate into endothelial-like cells in vitro and in vivo

Abstract: Vascular endothelial growth factor (VEGF) induces endothelial cell differentiation. To investigate the role of VEGF overexpression in regulating the phenotype of macrophages, we transfected mouse macrophages with human VEGF(165) and examined the expression of the genes and proteins for various endothelial markers. Macrophages overexpressing VEGF significantly expressed fetal liver kinase 1 (FLK-1), vascular endothelial cadherin (VE-cadherin), CD31, Von Willebrand factor (vWF), endothelial nitric oxide synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The ability of macrophages to transdifferentiate into endothelial cells, endothelial progenitor cells, or endothelial-like cells both in vitro and in vivo has been documented. 106,107 The generation of endothelial progenitor cells from macrophages is crucial given the fact that this aspect of macrophage plasticity could be used to stimulate the revascularization of injured blood vessels in ischemic tissues. Macrophages have also been shown to infiltrate the corneal stroma and transdifferentiate into lymphatic endothelial cells.…”
Section: Transdifferentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of macrophages to transdifferentiate into endothelial cells, endothelial progenitor cells, or endothelial-like cells both in vitro and in vivo has been documented. 106,107 The generation of endothelial progenitor cells from macrophages is crucial given the fact that this aspect of macrophage plasticity could be used to stimulate the revascularization of injured blood vessels in ischemic tissues. Macrophages have also been shown to infiltrate the corneal stroma and transdifferentiate into lymphatic endothelial cells.…”
Section: Transdifferentiationmentioning
confidence: 99%
“…108 By overexpression of vascular endothelial growth factor, macrophages can be stimulated to transdifferentiate to the endothelial cell type. 106 Pleiotrophin (PTN) expressed by macrophages under ischemic conditions can promote transdifferentiation of macrophages to endothelial cells both in vitro and in vivo. PTN-induced transdifferentiation of macrophages has been shown to be regulated at the transcription level by GATA-2 and GATA-3.…”
Section: Transdifferentiationmentioning
confidence: 99%
“…Similarly, various in vitro and in vivo experiments have indicated that monocytes themselves are capable of undergoing "vasculogenesis" and transform into cordlike structures that express endothelial markers like von Willebrand factor, CD31, vascular endothelial (VE)-cadherin, and CD105, following exposure to pro-angiogenic factors such as VEGFA and insulin-like growth factor 1. 37,38 In multiple myeloma, TAMs that express multiple endothelial markers cooperate with endothelial cells in the formation of the endothelial lining of tumor blood vessels. 39 The expression of endothelial lineage markers like VE-cadherin, VEGFR2, factor VIIIrelated antigen, and von Willebrand factor and the formation of capillary-like structures in vitro can also be induced in macrophages/monocytes in response to VEGFA, basic fibroblast growth factor, 40 or pleiotrophin 41 stimulation (Fig.…”
Section: Tams and Tumor Neovascularizationmentioning
confidence: 99%
“…Examples of such plasticity include transdifferentiation of macrophages to endothelial progenitor cells to support tissue vascularization. 21 Transdifferentiation of monocytes and macrophages to functional endothelial cells has been demonstrated by overexpression of proteins like vascular endothelial growth factor (VEGF) 21 and pleiotrophin. 22 This in vivo reprogramming of cellular identity using direct transdifferentiation strategies has been also demonstrated in the mouse brain, Figure 1 A schematic timeline of the history of regeneration, stem cell research, cellular transition, and cell reprogramming.…”
Section: Macrophage Fate At the Site Of Tissue Repairmentioning
confidence: 99%